THE EFFECT OF PROMOTION AND QUALITY OF SERVICE ON CUSTOMER SATISFACTION ON DAFIRA TOUR & TRAVEL - Yudhistira Adwimurti; Selfiani; Hendi Prihanto (Moestopo International Review on Social, Humanities, and Sciences, 2022)
The purpose of this study was to determine the effect of sales promotion and service quality on customer satisfaction at PT. Dhiya Alia Firdaus (Dafira Tour & Travel). This study uses a quantitative descriptive approach. The population of this study were 134 consumers who had made a purchase at Dhiya Alia Firdaus (Dafira Tour & Travel). The sample of this study used the Slovin formula as many as 100 respondents. Data collection techniques through questionnaires, documentation, literature studies and observations that have been tested for validity and reliability. Analysis of the data used in this study is the method used is multiple linear regression test with data management using SPSS Version 26. The results show that: (1) Promotion significantly affects consumer satisfaction. which means that the promotion variable is partially proven to affect consumer satisfaction. (2) Service Quality has a positive and significant effect on Consumer Satisfaction. which means that the service quality variable is partially proven to affect consumer satisfaction. (3) Promotion and Service Quality have a positive and significant effect on Consumer Satisfaction, which means that promotion and service quality variables simultaneously affect consumer satisfaction.